Modernizing financial institutions : an assessment of alternative moanetary regimes for a future Palestinian state : dollarization versus a national currency : selected literature review with case syudies of Ecuadoe and El Salvador - Karnovitz, Alan; Moldovan, Sonia; Menelaws, R.D; United States Agency for International Development; The Louis Berger Group (Washington, D.C USAID, 2010)
​This paper discusses the advantages and disadvantages of dollarization, occurrence in emerging economies, and economic performance of dollarized countries, especially Ecuador and El Salvador. The paper discusses dollarization in the Palestinian context and assesses the advantages and disadvantages of dollarizing the Palestinian economy compared to issuing a national currency (i.e., the Palestinian Pound) under a currency board or under a managed float regime.
​1. Introduction and Political Context -- 2. The Role of Central Banks and Monetary Regime Options -- 3. Definition of Full Dollarization, Partial Dollarization and their Occurrence in Emerging Economies -- 4. Benefits attributed to Dollarization -- 5. Costs attributed to Dollarization -- 6. Two Case Studies: Ecuador and El Salvador -- Ecuador -- El Salvador -- 7. Summary of Dollarization Impacts in Ecuador and El Salvador -- 8. Dollarization or a National Currency?
MFI- USAID contract - The Louis Berger Group
Includes bibliographical references
Keywords: Financial economics; FINANCIAL INSTITUTIONS; MONETARY SYSTEMS; CURRENCIES; IMPACT ASSESSMENT; PALESTINE; CASE STUDIES; ECUADOR; EL SALVADOR